2021
DOI: 10.3390/en14206802
|View full text |Cite
|
Sign up to set email alerts
|

Insurance Programs in the Renewable Energy Sources Projects

Abstract: The development of projects using renewable energy sources (RES) necessitates the development of insurance programs and systems. This involves identifying and assessing the risks of renewable energy projects in the transition to new types of energy, determining typical corporate and specific risks, the need and content of the main types, forms of insurance contracts, assessing the financial condition, and choosing insurance organizations and reinsurance programs. This article focuses on the formation of such i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…For a sustainable growth of the renewable energy market, Gatzert and Kosub (2016) indicated that the availability of adequate insurance solution is crucial for the investors to manage and mitigate the complex risks in renewable energy projects. Kirillova et al (2021) identified the specific risks to the renewable energy industry, analyzed the related insurance coverages, and pointed out a close interaction between insurance and technological advancement and a formal regulatory basis is vital to ensure the sustainable development of the renewable energy market.…”
Section: Insurance As Important Risk Management Tool In Renewable Ene...mentioning
confidence: 99%
“…For a sustainable growth of the renewable energy market, Gatzert and Kosub (2016) indicated that the availability of adequate insurance solution is crucial for the investors to manage and mitigate the complex risks in renewable energy projects. Kirillova et al (2021) identified the specific risks to the renewable energy industry, analyzed the related insurance coverages, and pointed out a close interaction between insurance and technological advancement and a formal regulatory basis is vital to ensure the sustainable development of the renewable energy market.…”
Section: Insurance As Important Risk Management Tool In Renewable Ene...mentioning
confidence: 99%